Phallic worship : a description of the mysteries of the sex worship of the ancients with the history of the masculine cross; an account of primitive symbolism, hebrew phallicism, bacchic festivals, sexual rites, and the mysteries of the ancient faiths. (S.l. : s.n., 1886)
Bibliotheek Camille Huysmans
Engels
Monografie
Keywords: religie; seksualiteit